2013
DOI: 10.3177/jnsv.59.503
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble Vitamin Deficiencies in Complicated Peptic Ulcer Patients Soon after Ulcer Onset in Japan

Abstract: SummaryWe investigated over time whether contemporary Japanese patients with complicated peptic ulcers have any water-soluble vitamin deficiencies soon after the onset of the complicated peptic ulcers. In this prospective cohort study, fasting serum levels of water-soluble vitamins (vitamins B1, B2, B6, B12, C, and folic acid) and homocysteine were measured at 3 time points (at admission, hospital discharge, and 3 mo after hospital discharge). Among the 20 patients who were enrolled in the study, 10 consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Additionally, Aditi and Graham [ 25 ] documented that Vitamin C (ascorbic acid) plays a very important role in the conservation and treatment of the gastric mucosa and that deficiency in vitamin C has repeatedly been linked with PUD. Our findings in women are consistent with the results of previous studies [ 22 , 24 , 25 ]. In this study, fiber, vitamin B2 (riboflavin), sodium, and ash were significantly associated with PUD in women in both the crude and adjusted analyses.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Additionally, Aditi and Graham [ 25 ] documented that Vitamin C (ascorbic acid) plays a very important role in the conservation and treatment of the gastric mucosa and that deficiency in vitamin C has repeatedly been linked with PUD. Our findings in women are consistent with the results of previous studies [ 22 , 24 , 25 ]. In this study, fiber, vitamin B2 (riboflavin), sodium, and ash were significantly associated with PUD in women in both the crude and adjusted analyses.…”
Section: Discussionsupporting
confidence: 94%
“…They argued that vitamin B2 and potassium were inversely associated with the risk of duodenal ulcer. Miyake and colleagues [ 24 ] reported that a lack of water-soluble vitamins could accelerate the development of PUD in Japanese adults. Additionally, Aditi and Graham [ 25 ] documented that Vitamin C (ascorbic acid) plays a very important role in the conservation and treatment of the gastric mucosa and that deficiency in vitamin C has repeatedly been linked with PUD.…”
Section: Discussionmentioning
confidence: 99%
“…Among the subjects who had been examined in our outpatient clinic, vitamin B 12 deficiency was 4.8% (83/1716 patients). The median vitamin B 12 concentration was 142 pmol/L (IQR 122–154) (normal range 172–674) [ 33 ]. The median MMSE before treatment (baseline) was 22 (IQR 15–26), median Hcy was 16.7 mmol/mL (IQR 12.0–27.7) (normal range 3.7–13.5), and median folate was 6.8 pg/mL (IQR 5.0–8.4) (normal range 3.6−12.9) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, intact gastrointestinal lining by gastric epithelium is one of the robust factors in gut defense and hence gut health (Pastorelli et al 2013). A cohort study conducted in Japan indicated that most patients with complicated peptic ulcers may have deficiency of one or more water-soluble vitamins including vitamin B 12 in the early phase of the disease before the onset of ulcer complications (Miyake et al 2013). It becomes therefore imperative to address the effect of vitamin B 12 deficiency during gastric ulcer condition and the status of ulcer during the treatment with vitamin B 12 enriched source, in this case, Spirulina platensis.…”
Section: Introductionmentioning
confidence: 99%